Development of Entrepreneurial and Marketing Capabilities in Engineering & Technology Based Firms - Qureshi, Shahid; kratzer, Jan (Mehran University Research Journal of Engineering and Technology; Vol 36 No 3 (2017): July Issue, 2017)
EM (Entrepreneurial Making) and MC (Marketing Capabilities) play a crucial role in the success of a firm. Many engineering and technology firms are run by people having an engineering degree which have less exposure to marketing. A strong EO (Entrepreneurial Orientation) enables the firm to carry out and develop its MC in opportunistic, proactive and innovative way. The EO and MC are shaped and defined by various antecedents i.e. technological and market turbulence, market and strategic orientation. The impact and influence of these antecedents vary as the organization moves from its infancy to growth and maturity. The following research tests the impacts of various antecedents during the various stages of the life cycle of the engineering and technology based firms. To conduct the longitudinal study, the engineering and technology firms were grouped in to four categories temporally i.e. (1) less than 2 years, (2) 3-4 years, (3) 5-8 years and (4) more than 9 years. This allowed a quasi longitudinal observation to find out and compare the changes over time. The results show that the various factors influence the MC in varying degree during the various stages of the life cycle of the firm.